NILAI KEARIFAN UNGKAPAN BUDAYA JAWA “RUKUN AGAWE SANTOSA” DALAM GAGASAN PEMIKIRAN EMMANUEL LEVINAS - Theresia Pratiwiningsih (JURNAL ILMU BUDAYA, 2020)
The focus of this research is the theme of Javanese local wisdom culture which related to Javanese proverb expressions about "Rukun Agawe Santosa". My aim is to explore further how these Javanese proverbs are carried out by the Javanese people themselves in daily life. To deepen this study the methodology that I used was Comparative Study with an awareness of the ethical values and harmony that was sparked in the Javanese proverb expression "Rukun Agawe Santosa". Through Emannuel Levinas's thoughts on Ethics and in the expression of Javanese local wisdom culture, I find that the value of environmental ethics is growing today due to the emergence of a stronger awareness of the importance of maintaining relationships with "the other" ie the earth and all its contents but in general, ethics are the most talked about in the context of human relations and ultimately the Javanese cultural expression "Rukun Agawe Santosa" becomes the main capital and the most appropriate way of creating solid unity and unity so as to create a strong and peaceful society.